Progress of Photodetectors Based on the Photothermoelectric Effect - Lu, Xiaowei; Sun, Lin; Jiang, Peng; Bao, Xinhe (Advanced materials (Weinheim), 2019)
High‐performance uncooled photodetectors operating in the long‐wavelength infrared and terahertz regimes are highly demanded in the military and civilian fields. Photothermoelectric (PTE) detectors, which combine photothermal and thermoelectric conversion processes, can realize ultra‐broadband photodetection without the requirement of a cooling unit and external bias. In the last few decades, the responsivity and speed of PTE‐based photodetectors have made impressive progress with the discovery of novel thermoelectric materials and the development of nanophotonics. In particular, by introducing hot‐carrier transport into low‐dimensional material–based PTE detectors, the response time has been successfully pushed down to the picosecond level. Furthermore, with the assistance of surface plasmon, antenna, and phonon absorption, the responsivity of PTE detectors can be significantly enhanced. Beyond the photodetection, PTE effect can also be utilized to probe exotic physical phenomena in spintronics and valleytronics. Herein, recent advances in PTE detectors are summarized, and some potential strategies to further improve the performance are proposed. The room‐temperature detection of long‐wavelength infrared and terahertz radiation can be realized by photothermoelectric (PTE) detectors. The responsivity and the response speed of PTE‐based photodetectors have made impressive progress with the discovery of novel thermoelectric materials and the development of nanophotonics. Beyond light detection, the PTE effect can be utilized to study novel physical phenomena in spintronics and valleytronics.